Growth analysis in relation to sowing dates in four varieties of wheat: a functional approach - Haider, SA (Journal of Life and Earth Science, 2011)
Effect of three different sowing dates on growth of four varieties of wheat was analyzed using functional techniques. Crop growth rate (CGR), relative leaf growth rate (RLGR) and specific leaf area (SLA) were higher in the early sown plants compared to late sown plants. Net assimilation rate (NAR) in all the varieties increased slowly at the early stages of growth while it increased sharply at the later stages with fluctuations in most cases. The declining tendency was found in SLA at the middle stage of growth except variety C 306. Higher values of CGR were found in the early sown Protiva, leaf weight ratio (LWR) in the late sown C 306 and early sown Opata, RLGR in the early sown Opata and C 306, SLA in the late sown Opata and Protiva and NAR in all the four varieties when they were sown late. Key words: Wheat; sowing date; growth; functional technique DOI: 10.3329/jles.v2i2.7492 J. Life Earth Sci., Vol. 2(2) 17-25, 2007